Exploring farmer preferences towards innovations in the vanilla supply chain. (1st January 2022) - Watteyn, Charlotte; Dejonghe, Olivia; Van Hoyweghen, Kaat; Azofeifa Bolaños, José Bernal; Karremans, Adam P.; Vranken, Liesbet; Reubens, Bert; Muys, Bart; Maertens, Miet
Abstract: The vanilla supply chain is characterized by high risk crop management and unstable supply. In order to meet global vanilla demand while improving production sustainability, new approaches considering agro-ecological cultivation systems and transparent supply chain management are needed. In this study, we aim to understand farmers' preferences towards such alternative vanilla cultivation and marketing systems, and thereby inform the development of a more sustainable vanilla supply chain. We implemented a discrete choice experiment and a survey with 186 farmers in the Península de Osa, southern Costa Rica, and estimated mixed logit and latent class models. We find that surveyed farmers are in general positive about vanilla cultivation and prefer an agroforestry system over vanilla cultivation in forests, crop wild relatives over commercial species, and manual pollination over natural pollination. Farmers prefer to sell green rather than cured vanilla beans, and like to engage in cooperatives that provide training and production contracts with buyers. Preferences are found to differ across farmers and we identify four preference classes. The preference class with the largest average probability (44%) shows the strongest preferences for agro-ecological vanilla cultivation in diversified agroforestry systems, using crop wild relatives and natural pollinators. Furthermore, this class has the highest likelihood to live in areas with restricted land use policies, creating opportunities for the development of more sustainable vanilla cultivation systems conform with the national program of landscape connectivity and biodiversity conservation. We propose a two-tier approach in alignment with observed farmer preferences and with potential for upscaling to similar areas along the Neotropics. Graphical abstract: Image 1 Highlights: Discrete choice experiment on farmer preferences for vanilla production in Costa Rica. Positive but heterogeneous attitudes of farmers towards vanilla cultivation. Agro-ecological production and market contract preferred by farmers in fragile areas. Farmers interested in vanilla crop wild relatives and natural pollination. Proposition of vanilla program, with potential upscaling to other Neotropical regions.